Expanding Access to Basic Services in Asia and the Pacific Region: Public-Private Partnerships for Poverty Reduction - Adrian T. Panggabean (Asian Development Bank (ADB), 2006)
This paper argues that the public–private partnership (PPP) fi nancing modality can work for the poor. To achieve this outcome, governments need to fi rst create the appropriate enabling environment for PPPs to work, and then take further steps to ensure pro-poor benefi ts of infrastructure provision. The paper defi nes what PPP is and highlights the types of PPPs that fall under that defi nition: from service or contract management to full-scale privatization with many models in between. Using ADB's own experience in several countries and in different projects, the paper suggests four key steps to make PPPs work for the poor. First, integrate PPPs into the governments' poverty reduction strategies, interpret such strategies as a form of "market research", and use them as "marketing opportunities." Second, weave poverty considerations into the PPP policy setting and process. This step involves geting the PPP framework right, and combining this with the universal service objectives of infrastructure provision, competitive service delivery, and careful design of tariff policy. Third, pro-poor regulatory design and enforcement should be put in place to help make PPPs work for the poor. Finally, the fi nancing structure of PPPs should be taken care of because asymmetrical allocation of fi nancing risks can weigh heavily on the poor.
hdl:11540/1881
Keywords: 330